Synthesis and characterization of UV-curable cellulose acetate butyrate-based oligomers and their cotton fabric coatings - BOZTOPRAK, YALÇIN; YILDIZ, ZEHRA (SPRINGER, 2021)
In order to improve the thermal stability and flexibility, cellulose acetate butyrate (CAB) was modified with toluene diisocyanate-hydroxyethyl methacrylate (TDI-HEMA) adduct in various molar ratios. The obtained oligomer was characterized by proton nuclear magnetic resonance (H-1 NMR) and Fourier transform infrared (FTIR) spectroscopies. Gloss, cross-hatch, contact angle, and Taber abrasion tests were all used to investigate the film forming performance of the modified CAB oligomers on glass plates. The UV-cured free films of the synthesized oligomers were examined in terms of the mechanical tests. By using the synthesized CAB oligomers, coating formulations were prepared and applied onto cotton fabrics in order to make the cotton fabrics more durable in outdoor environments. The existence of the coating layer on the fabric surfaces was investigated by scanning electron microscopy (SEM). The coated UV-cured fabrics were evaluated separately in terms of abrasion, thermal conductivity, and air and water vapor permeability properties. Results proved that the oligomer (50%-CAB) in which 50% of the hydroxyl groups of CAB were reacted with TDI-HEMA adduct showed the best mechanical properties with the highest tensile strength and modulus values. Considering the coated fabrics, the least deformation against abrasion, the highest air/water vapor permeability, and the best thermal conductivity were all recorded in 50%-CAB coated sample.
Keywords: Cellulose acetate butyrate; UV-curing; Cotton fabric; Thermal resistance; Air; water vapor permeability